Nanocarbon-based catalysts for esterification: Effect of carbon dimensionality and synergistic effect of the surface functional groups - Zhang, Honglei; Luo, Xiang; Shi, Kaiqi; Wu, Tao; He, Feng; Yang, Hangqi; Zhang, Shanshan; Peng, Chuang (Elsevier, 2019)
Carbon-based solid acid catalysts represented outstanding hydrothermal and mechanical properties but lower catalytic performances and stabilities. Therefore, more comprehensive investigations should be conducted to optimize their catalytic performances. The correlations between catalytic performance, carbon dimensionality and composition of oxygen-containing functional groups of nanocarbon-based catalysts were investigated. The dimensionality of carbon materials had notable effect on the catalytic reactivity and the layered 2-D structure could maximize the solid/liquid interface and minimize the mass transfer resistance and thus favor the catalytic esterification. GO-50, prepared with 50 mL concentrated H2SO4, exhibited outstanding catalytic activity and had 3 times higher turnover frequency (TOF) value than that of H2SO4. In GO-50, the -SO3H groups were identified as the primary catalytic active sites, while the carboxyl groups enhanced the inherent activity of -SO3H, thus facilitating the esterification. The -COOH/-SO3H molar ratio played significant roles and desirable -COOH/-SO3H molar ratio would promote esterification significantly. The esterification kinetics catalyzed by GO-50 was studied and the apparent activation energy of esterification by GO-50 is 1.5 times lower than that by H2SO4. The esterification mechanism by GO-50 was also proposed. Furthermore, GO-50/Poly (ether sulfones) (PES) membrane was prepared and employed in esterification and the optimal reaction conditions were systematically studied.